Analisis Perbandingan Block Cipher Simon-Speck, Simeck, Skinny pada Komunikasi Berbasis LoRa - Putri, Winda Ezranata; Favian Dewanta; Farah Afianti (POLITEKNIK NEGERI JAKARTA, 2022)
Inventions solving problems through the incorporation of technology and social impacts to facilitate human life can be defined as the Internet of Things (IoT). Security and privacy are challenges in various Internet of Things applications given the rapid growth of IoT devices. Meanwhile, IoT devices still do not have sufficient communication security. Communication systems on IoT devices require cryptographic to maintain the security of their communications. The appropriate algorithm to be implemented on IoT devices should be the smallest and fastest lightweight cryptographic algorithm or commonly called Lightweight Cryptography because IoT devices have limited memory and computing power. In this study, the proposed algorithm to be implemented in Long Range or LoRa-based IoT devices is the Simon-Speck, Simeck, and Skinny encryption algorithm. This study discusses the implementation of the Simon-Speck, Simeck, and Skinny algorithms on Long Range-based IoT devices. The parameters compared are the computation time of the encryption and decryption process and the avalanche effect value. In the encryption and decryption process, the Speck algorithm has the fastest computation time. Meanwhile, the highest avalanche effect value is obtained by the Skinny algorithm, which is 50.34%.